KARAKTERISTIK KOMITMEN PADA PASANGAN SUAMI ISTRI MUSLIM DENGAN KONDISI INFERTILITAS (USIA PERNIKAHAN 5-21 TAHUN) - Mahardika, Dwita Putri; Ganjar, Adi (MANASA, 2023)
This study aim is to find out about the commitment and characteristic of married couples who experience infertility. Nowadays, getting married and producing offspring is still a social demand in society. This also still happening in Indonesia. As the country with the largest Muslim population in the world, many people decide to get married for religious and hereditary reasons. Unfortunately, not everyone can easily produce offspring after marriage. For people who experience infertility, the demand to have children able to trigger conflicts in their domestic life. In addition, the psychological dynamics that occur are often not easy to deal with, while trying to produce offspring. To get through this experience, couples need strong commitment. Types of commitment are divided into personal, moral, and structural commitments. This study is a descriptive qualitative study involving four married couples with a marriage age of 5-21 years. The data collection technique was conducted by semi-structured interviews. The results showed that all three aspects of commitment appeared in the participants, namely personal, moral, and structural commitment. Additional research results also revealed that aspects of religiosity played a role in generating commitment to maintain marriage in four pairs of participants. Keywords: married couples, infertility, commitment, offspring.